Kajian Psikoanalisis Sigmund Freud Berbasis Novel Karya Tulus Setiyadi untuk Menangani Kecemasan - Habsy, Bakhrudin All; Tarigan, Kevin Leonardo; Assalsabila, Farikh; Indriyani, Auriza Fitri; Arisa, Ayu Jingga (TSAQOFAH, 2024)
Anxiety is one of the most common psychological problems experienced by everyone. The novel Kasrimpet Piweling and Puspita Rinengga by Tulus Setiyadi is one of the literary works that raises the issue of anxiety for its characters. Therefore, this research will discuss the anxiety of the main character in the novels Kasrimpet Piweling and Puspita Rinengga by Tulus Setiyadi using the psychoanalytic view proposed by Sigmund Freud. This research aims to explain the anxiety experienced by the main character in both novels. The theory used in this research is Sigmund Freud's psychoanalysis theory. Data collection with literature study method using library techniques, reading, recording and classification. Data analysis is done by looking at the personality structure, anxiety and ego defense mechanisms used by the characters. This type of research is literary research using descriptive method. The research data are in the form of words, phrases, clauses, sentences, narration from the narrator, characters' speech, and characters' actions related to ego defense mechanisms in Kasrimpet Piweling and Puspita Rinengga novels. The data collection techniques in this research are as follows: (1) conducting a literature study, (2) reading and understanding the novel, (3) marking the parts of the novel that indicate id, ego, and super ego (4) identifying the main characters and additional characters in the novel, (5) recording the data in the novel.